R3 versus R4 Thoracoscopic Sympathectomy for Severe Palmar Hyperhidrosis - Zhang, Wenxiong; Wei, Yiping; Jiang, Han; Xu, Jianjun; Yu, Dongliang (The Thoracic and Cardiovascular Surgeon, 2017)
Background Thoracoscopic sympathectomy (TS) was the preferred surgical treatment for palmar hyperhidrosis (PH), but postoperative complications such as compensatory sweating (CS) were common. This study was projected to compare R3 versus R4 TS for treating severe PH.Methods From April 2009 and March 2015, 106 consecutive patients with severe PH underwent bilateral R3 (n = 62) or R4 (n = 44) TS at The Second Affiliated Hospital of Nanchang University. The patients were followed up to evaluate symptom resolution, postoperative complications, satisfaction level, and severity of CS.Results The 106 patients underwent 212 sympathecotomies and were cured with no severe complications or perioperative mortality. The incidence of minor side effects (such as pneumothorax, gustatory sweating, moist hands, and bradycardia) was similar in both groups. More patients had overdry hands in the R3 group than in the R4 group (6/62 vs. 0/44; p = 0.040). More CS occurred in the R3 group as compared with the R4 group (42/62 vs. 23/44; p = 0.156). The incidence of moderate-to-severe CS was higher in the R3 group than in the R4 group (14/62 vs. 4/40; p = 0.045). Most patients were satisfied with the results, except for three (5.84%) in the R3 group and one (2.27%) in the R4 group.Conclusion PH can be effectively treated by either R3 or R4 TS, with high rates of patient satisfaction. R4 sympathectomy appears to be associated with less severe CS and should be the choice of denervation level.
Keywords: thoracoscopy; sympathectomy; palmar hyperhidrosis; compensatory sweating